2012
DOI: 10.1111/j.1540-8175.2011.01651.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial Anomalous Left Pulmonary Artery along with Aortic Coarctation in an Infant with Kabuki Syndrome

Abstract: We report an antenatally diagnosed fetal coarctation delivered prematurely and confirmed to have coarctation as well as additional nonobstructing anomalous left pulmonary artery branch (aLPA) from right pulmonary artery (RPA) and significant dysmorphic features. The baby underwent an uncomplicated arch repair, but had numerous multisystem and growth related issues prompting a diagnosis of Kabuki syndrome (KS) at 1 year of age. While coarctation and hypoplastic left heart syndrome are observed in this syndrome,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Totally 76 cases of KS were reported to be associated with congenital heart defects by 19 reports [6,7,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Of them, the gender was expressed in 37 patients including 17 males and 20 females with a male-to-female ratio of 0.85:1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Totally 76 cases of KS were reported to be associated with congenital heart defects by 19 reports [6,7,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Of them, the gender was expressed in 37 patients including 17 males and 20 females with a male-to-female ratio of 0.85:1.…”
Section: Resultsmentioning
confidence: 99%
“…Three patients with hypoplastic left heart were males, and 2 were females, and 1 of the females was with perimembranous subaortic ventricular septal defect [24]. Bhat et al [25] reported a wide variety of cardiac malformations (31-58%) seen in this syndrome, the most common of them being aortic coarctation (29%). Of greater interest, Digilio et al [12] categorized the congenital heart defects associated with KS into 7: (1) left-sided obstructions: aortic coarctation 8 (22.8%), aortic stenosis 2 (5.7%); (2) septal defects: ventricular septal defects 6 (17.1%), secundum atrial septal defects 7 (20%); (3) right--sided obstructions: pulmonary stenosis 1 (2.8%); (4) extracellular matrix defects: atrioventricular canal, complete 2 (5.7%); (5) outfl ow/conotruncal defects: tetralogy of Fallot 4 (11.4%), double outlet right ventricle 1 (2.8%), d-transposition of the great arteries with intact ventricular septum 1 (2.8%); (6) targeted growth defects: partial anomalous pulmonary venous return 2 (5.7%); and (7) cell death defects: Ebstein's anomaly 1 (2.8%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21] Nevertheless, there are some reports addressing associated rare great vessels anomalies such as partial anomalous left pulmonary artery,[4] partial anomalous right pulmonary venous drainage with dilatation of main pulmonary artery and aorta,[10] and double aortic arc. [14] Other rare vascular anomalies also include tortuous retinal vessels and Galen vein dilatation;[917] however, occlusion of an ICA with KS is unprecedented.…”
Section: Discussionmentioning
confidence: 99%
“…A few articles met the review criteria. [246910141718] Other articles were included by decision of the authors aiming to improve discussion.…”
Section: Case Reportmentioning
confidence: 99%